The Effect of Covid-19 on BIST-100 and Exchange Rates Influencing Businesses - İslamoglu, Mehmet; Yetgin, Muhammed Ali; Kayhan, Fatih (Muş Alparslan Üniversitesi, 2021)
Covid-19, appearing first in City of Wuhan in People's Republic of China in December 2019, infected all continents, regions and countries in a very short period. Covid-19 influenced the humanity in terms of health, economic and social aspects. The effect of Covid-19 on the economy is studied in this research. Businesses are considered as one of the most important actors of the country's economy. Investments in stocks, stock exchange and exchange rates determine the activities of businesses. The effects of Covid-19 pandemic on exchange rates (USD/TL and EURO/TL) and BIST-100 are examined in this study. E-views 9.0 statistical program is used in this research. Phillips-Perron unit root test and multiple regression tests are employed in the analyses. The study concludes by suggesting that Covid-19 daily number of cases and number of patients that recover the pandemic have significant effect on USD/TRY, EUR/TRY and BIST-100, which are leading economic and financial indicators as far as Turkey is concerned.

Covid-19, appearing first in City of Wuhan in People's Republic of China in December 2019, infected all continents, regions and countries in a very short period. Covid-19 influenced the humanity in terms of health, economic and social aspects. The effect of Covid-19 on the economy is studied in this research. Businesses are considered as one of the most important actors of the country's economy. Investments in stocks, stock exchange and exchange rates determine the activities of businesses. The effects of Covid-19 pandemic on exchange rates (USD/TL and EURO/TL) and BIST-100 are examined in this study. E-views 9.0 statistical program is used in this research. Phillips-Perron unit root test and multiple regression tests are employed in the analyses. The study concludes by suggesting that Covid-19 daily number of cases and number of patients that recover the pandemic have significant effect on USD/TRY, EUR/TRY and BIST-100, which are leading economic and financial indicators as far as Turkey is concerned.
anemon
Keywords: Covid-19; Pandemy; BIST 100; Euro; US Dollar; Covid-19; Pandemy; BIST 100; Euro; US Dollar